New Classification Results on Surfaces with a Canonical Principal Direction in the Minkowski 3-space - Kelleci, Alev; Ergut, Mahmut; Turgay, Nurettin Cenk (Univ Nis, Fac Sci Math, 2017)
In this paper, we characterize and classify all surfaces endowed with canonical principal direction relative to a space-like and light-like, constant direction in the Minkowski 3-space.
Keywords: Minkowski space; Lorentzian surfaces; canonical principal direction